THE INFLUENCE OF LOCAL COMMUNITY CULTURE ON GLOBAL MARKETING - Tri Waluyo; Rahayu Lestari; Resti Hardini; Kumba Digdowiseiso; Siti Falindah Padlee (PT. Radja Intercontinental Publishing, 2024)
This literature study aims to address the global marketing challenges by examining the impact of local community culture. The individual's background exemplifies the intricate interplay between indigenous culture and worldwide marketing tactics. This research employs a Systematic Literature Review (SLR) to examine six decisions in Global Product Policy. It elucidates the impact of local culture on communication, negotiation, and consumer preferences in international markets. The results of the SLR indicate that the adaptation of product, language, and cultural symbols is essential in order to prevent misinterpretation and to ensure that the product remains relevant and appealing. The findings entail the implementation of strategies to accommodate variations in local cultural norms and values, as well as the significance of conforming to local government regulations and policies. The research findings indicate that preserving local community culture in global marketing necessitates an approach that is both sensitive and responsive. This study highlights the imperative for companies to comprehend, esteem, and adjust to indigenous culture in order to establish robust connections with consumers, enhance competitiveness, and attain enduring prosperity in an ever more interconnected global market.